Immunomodulation of MSCs and MSC-Derived Extracellular Vesicles in Osteoarthritis - Zhao, Xige; Zhao, Yanhong; Sun, Xun; Xing, Yi; Wang, Xing; Yang, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis (OA) has become recognized as a low-grade inflammatory state. Inflammatory infiltration of the synovium by macrophages, T cells, B cells, and other immune cells is often observed in OA patients and plays a key role in the pathogenesis of OA. Hence, orchestrating the local inflammatory microenvironment and tissue regeneration microenvironment is important for the treatment of OA. Mesenchymal stem cells (MSCs) offer the potential for cartilage regeneration owing to their effective immunomodulatory properties and anti-inflammatory abilities. The paracrine effect, mediated by MSC-derived extracellular vehicles (EVs), has recently been suggested as a mechanism for their therapeutic properties. In this review, we summarize the interactions between MSCs or MSC-derived EVs and OA-related immune cells and discuss their therapeutic effects in OA. Additionally, we discuss the potential of MSC-derived EVs as a novel cell-free therapy approach for the clinical treatment of OA.